THE MORAL CONSEQUENCES OF ALCOHOL CONSUMPTION (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the spiritual and moral crises, the weakening of national values, and the damage caused to the social environment as a result of the increase in alcohol consumption in society.
Keywords: Alcohol consumption, spiritual damage, moral crisis, family institution, national values, social environment, upbringing, spirituality policy, Uzbekistan.